Financial accounting - Williams, Jan R.; Bettner, Mark S.; Carcello, Joseph V. (McGraw-Hill Education, 2021)
"Financial Accounting was the FIRST text to illustrate Balance Sheet and Income Statement transactions using the four-step process described below. This hallmark coverage has been further revised and refined in the 18th edition. The Williams team breaks down the Accounting Cycle into three full chapters to help students absorb and understand this material: recording entries (Chapter 3), adjusting entries (Chapter 4), and closing entries (Chapter 5)"--